On Studying the early historical sources: The Epistle of Khalf b. Ziyad al-Bahrani - Salimi, Abdulrahman al- (2022)

From the First Renaissance to the Second: The Historical and Legal Basis for the Sultanate - Salimi, Abdulrahman al- (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Al-Salimi, Abdulrahman: On the Reception of Early Ibadi Theology. A Commentary on the Book on Monotheism by ‘Abd Allāh b. Yazīd al-Fazārī (2nd/8th Century). - Metzler, Berenike (Orientalistische Literaturzeitung, 2022)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Recension

Sultan Qaboos and modern Oman, 1970-2020 - Fromherz, Allen James; Salimi, Abdulrahman al- (Edinburgh University Press, 2022)
This is the first, timely account of the modern Oman over the entire reign of Sultan Qaboos (1970-2020). The book provides unique, wide-ranging interdisciplinary and international perspectives on modern Oman by specialists in a variety of fields from Oman, Europe and North America. Utilising a range of perspectives, all chapters connect to the theme of rebirth, of the connections between the past and the future pursued by Sultan Qaboos and his government in fields as diverse as health, religion, law, economy, heritage and diplomacy. Not overlooking the many challenges faced during Sultan Qaboos' reign and still faced by Oman, the book engages various theories and perspectives about Oman's economic, religious, educational and cultural transformations under Qaboos (d. 2020 CE)
Keywords: Vie politique – Oman – 1970-2020

Constitutional Reforms During the Reign of Sultan Qaboos - Kharusi, Salim al- (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

“Friend to All, Enemy to None”: Oman’s Quiet Diplomacy Since 1970 - Owtram, Francis (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Politique étrangère – Oman – 1970-2020

Public Health and the Omani Renaissance - Foley, Sean (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Omani Peacemaking and Middle East Crises in the 2010s: Sultan Qaboos’ Last Decade - Cole, Juan (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Politique étrangère – Oman – 1970-2020

Beyond the Horizon and Back: The Sultan Qaboos Scholarship - Pritt, Jody (Sultan Qaboos and modern Oman, 1970-2020, 2022)

Introduction: Sultan Qaboos, Omani Society, and the “Blessed Renaissance”, 1970–2020 - Fromherz, Allen (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

The Land of Frankincense: Dhofari Sites as National and World Heritage - Lewis, Krista (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Monuments – conservation – Oman

The Legacy of Sultan Qaboos: A Historiographical Note - Rabi, Uzi (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Duqm and Salalah: Oman’s Ports and Special Economic Zones - Kinnier, Jeffrey (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Ports – Oman

Muscat and Sultan Qaboos: The Omanization of Muscat and the Muscatization of Oman - Guirado Alonso, Javier (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

In the Middle of a Reign - Hoffman, Valerie J. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Prehistoric Interactions between Oman and the Indus Civilization: Projecting the Past in the Present - Kenoyer, Jonathan Mark (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Relations – Oman – Inde

The Interpretation of Islam under Sultan Qaboos - Hoffman, Valerie J. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Ibadisme – Oman

Greening Oman: Islamic Environmentalism, Sustainable Development, and Post-Oil Futures - Curtis, Maria F. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Développement durable – Oman

Nation and State in Oman: The Initial Impact of 1970 - Peterson, John E. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Literature in Oman During the Reign of Sultan Qaboos - Michalak-Pikulska, Barbara (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Littérature – Oman

Stamps as Messengers of the Renaissance: The Postal Issues of Oman During the Reign of Sultan Qaboos - Allen, Jr, Calvin H. (Sultan Qaboos and modern Oman, 1970-2020, 2022)

The Multiple Legacies of Sultan Qaboos: Heritage and Omani Nation Building - Penzier-Hightower, Victoria; Worrall, James (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020